Ultrastructural Changes of Hevea brasiliensis Muell.-Arg. Seeds during Imbibed Storage - Normah, M. N; Chin, H. F. (1989)
Ultra structural changes were observed in Hevea seeds stored at 10C, 22C and 27C Membrane degeneration appeared to be the most common feature of deterioration. At all storage temperatures, the plasma lemma was observed to be increasingly folded, disintegrated or withdrawn from the cell wall. The dissolution of the tonoplast was also widely observed.